Fabrication of (Ba, Na)Fe2As2 round wires and tapes using HIP process. (July 2020) - Miyawaki, D; Pyon, S; Awaji, S; Kajitani, H; Koizumi, N; Kito, H; Ishida, S; Yoshida, Y; Tamegai, T
Abstract: We fabricated round wires and tapes of (Ba, Na)Fe2 As2 using hot isostatic press (HIP) process, and evaluated their critical current density ( Jc ). Polycrystalline powders were synthesized by two methods by mixing raw materials in a planetary ball mill or by using pre-synthesized precursors (BaAs, NaAs, Fe2 As). Transport Jc of best wire reached 95 kA/cm 2 under self-field and 40 kA/cm 2 at 100 kOe. We also fabricated HIP tapes using the same powder and discuss their detailed characterizations. In particular, X-ray diffraction is extensively applied to the evaluation of the degree of texturing of the tape, and discuss its relationship with J c .